2019
DOI: 10.1002/nau.24019
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety severity does not influence treatment outcomes in patients with interstitial cystitis/bladder pain syndrome

Abstract: Aims Patients with interstitial cystitis/bladder pain syndrome (IC/BPS) typically experience anxiety mood status, which is closely connected with physical and psychological status and treatment outcome. This study aimed to evaluate the impact of anxiety severity on therapeutic results in IC/BPS patients. Methods We prospectively enrolled IC/BPS patients who had previously undergone any kind of treatment for their disease. The primary endpoint was a change in Beck Anxiety Inventory (BAI) scores at 3 months afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The self-report IC/BPS symptom and problem index (OSS) might be more related to the psychological condition rather than the bladder conditions, causing an increase in the patient's anxiety status score (BAI) with PFMP. 6 Likewise, the GRA score also has a signi cant association with different PFMP severities. This result has repeatedly demonstrated that self-report treatment outcomes are closely related to PFM conditions, such as in the ICSI (p = .029), ICPI (p = .007), and even GRA (p = .015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The self-report IC/BPS symptom and problem index (OSS) might be more related to the psychological condition rather than the bladder conditions, causing an increase in the patient's anxiety status score (BAI) with PFMP. 6 Likewise, the GRA score also has a signi cant association with different PFMP severities. This result has repeatedly demonstrated that self-report treatment outcomes are closely related to PFM conditions, such as in the ICSI (p = .029), ICPI (p = .007), and even GRA (p = .015).…”
Section: Discussionmentioning
confidence: 99%
“…5 Our previous study also demonstrated that stress is positively associated with pain in patients with IC/BPS, while stress reduction can lead to a simultaneous decrease in the severity of other symptoms. 6 Pelvic oor muscle (PFM) is often associated with urological, gynecological, gastrointestinal, and sexual problems and chronic pelvic pain. 8 Several researchers also noted that PFM hypertonicity (PFH), also called pelvic oor myofascial pain (PFMP), could affect treatment outcome and quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychological stress had been shown to be associated with exacerbation of IC symptoms involving pain and inflammation, not only associated with physiological damage but also negatively affecting psychological stress, and leading to poor quality of life (QoL) due to the current absence of effective long-lasting treatment [ 4 ]. Appropriate treatment should be conducted hierarchically and should combine multiple approaches, starting from lifestyle modification, followed by bladder therapy, accompanied by psychological adjustment and coping support [ 2 , 4 , 5 , 6 ]. The goal of managing patients with IC/BPS is to provide symptom relief and help patients achieve acceptable QoL post-treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%